REGULATING THE NON-MILITARY USE OF DRONES AND PROTECTION OF PRIVACY - Adnan Duraković; Sabina Duraković (Revija za kriminologiju i krivično pravo)
In last few years we are witnesses of strong development of drones’ capacity not only for military purposes but also for civilian use, particularly for police surveillance, investigations, arrests and search and rescue operations. Up until now not even United States of America adopted unified laws considering the use of drones and their impact on privacy but it is obvious that legal, administrative and justice framework for balancing these two conflicted interests and demands will soon be developed. This article will give the review of legal problems and solutions from literature covering countries which are the leaders in this field of technology and law.